1999
DOI: 10.1038/sj.onc.1202285
|View full text |Cite
|
Sign up to set email alerts
|

The community effect in FGF-1 mediated tumor progression of a rat bladder carcinoma does not involve a direct paracrine signaling

Abstract: A community e ect was found to occur between heterogeneous tumor cell populations leading to an overall increased tumorigenicity without a clonal dominance of the more tumorigenic clone. In the rat bladder carcinoma cell line NBT-II, this e ect appears mediated by the Fibroblast Growth Factor-1 (FGF-1) through either a direct or an indirect signaling pathway. Neovascularization induced by FGF-1 was found not to be responsible for the community e ect. The present study shows that the community e ect does not in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Non-resistant tumor cells also favor the growth of TSP1-resistant ones: when TSP1 was turned on after 18 d in tumors, when cells had divided about 12 times and the heterogeneity of the cell population had thus increased, resistance developed more rapidly than when TSP1 was expressed starting on day 0. Multiple clonal variants would cooperate during tumor progression through "community" effects (Jouanneau et al 1999) involving secreted factors, cell-cell interactions, or both. Resistance to TSP1, as it results among others in an increased secretion of angiogenic factors, would be one of the mechanisms involved in these community effects.…”
Section: Discussionmentioning
confidence: 99%
“…Non-resistant tumor cells also favor the growth of TSP1-resistant ones: when TSP1 was turned on after 18 d in tumors, when cells had divided about 12 times and the heterogeneity of the cell population had thus increased, resistance developed more rapidly than when TSP1 was expressed starting on day 0. Multiple clonal variants would cooperate during tumor progression through "community" effects (Jouanneau et al 1999) involving secreted factors, cell-cell interactions, or both. Resistance to TSP1, as it results among others in an increased secretion of angiogenic factors, would be one of the mechanisms involved in these community effects.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the episialin-negative cells are not refractory to ET-18-OMe can be due to the "community effect" described for mixed cell populations with one type of cell dominating the other via cell-cell interactions. 41 Indeed, in a mixture with a minority of MCF7/AZ and a majority of MCF7/6 cells, the MCF-7/AZ phenotype dominates and cells become adhesion-proficient (M. Bracke, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…The constitutive expression of FGF-1 or FGF-2 by these carcinoma cells generates cells that secrete the corresponding growth factor and that in vivo allow the growth of highly vascularized tumors as well in autocrine or nonautocrine NBT-II-expressing cells (Jouanneau et al, 1997;Billottet et al, 2002). However, a major difference in growth rate was observed: tumors developing NBT-II cells expressing FGF-2 grew like the control, whereas the growth rate of FGF-1-expressing cells was much faster (Jouanneau et al, 1997(Jouanneau et al, , 1999. Although constitutive expression of the high-affinity receptor FGFR-1 gave cells that have acquired the capacity to be activated by exogenous FGF-2, these cells induced tumors with growth properties similar to that of parental cells (Moscatelli, 1992); conversely, when they are engineered to constitutively express FGFR-1 and FGF-2, they behave like FGF-1-producing cells (Billottet et al, 2002).…”
Section: Introductionmentioning
confidence: 74%
“…Previously, we showed that tumors derived from FGF-1-transfected NBT-II cells grew faster than tumors obtained with control or FGF-2-transfected cells, irrespective of their angiogenic status (Jouanneau et al, 1997(Jouanneau et al, , 1999. Furthermore, NBT-II cellsengineered autocrine for FGF-2 became highly tumorigenic but present the same tumor vascularization (Billottet et al, 2002).…”
Section: Discussionmentioning
confidence: 99%